In Individuals with Osteogenesis Imperfecta, Cephalometric Findings Suggest that Bisphosphonate Therapy May Improve Craniofacial Growth - Tuurala, Henri; Waltimo-Sirén, Janna; Valta, Helena; Arponen, Heidi (Springer Science and Business Media LLC, 2026)
Osteogenesis imperfecta is a rare hereditary condition affecting type 1 collagen formation. Among the wide spectrum of phenotypic features, osteogenesis imperfecta variably impairs craniofacial growth, affecting facial morphology and predisposing to malocclusion. At present, bisphosphonates are the gold standard for treatment of osteogenesis imperfecta, but knowledge on the effect of the medication on craniofacial growth is lacking. This retrospective study analysed lateral skull radiographs of 36 growing individuals with osteogenesis imperfecta and bisphosphonate treatment history (mean age 10.0 years, 13 females). Of them, 23 had been diagnosed with type I, 8 with type III, and 5 with type IV osteogenesis imperfecta. The historical control group that had not received bisphosphonate therapy comprised 34 individuals (mean age 8.1 years, 22 females) with osteogenesis imperfecta, type I in 18, type III in 7, and type IV in 9 individuals. The cephalometric measurement values were converted into age- and sex-matched Z-scores based on normal population values of the same ethnicity. Inter-group comparisons of the Z-scores showed several statistically significant differences where the bisphosphonate treatment group deviated less from unaffected population than the historical group. These included one or more of the mandibular size measurements in all studied types of osteogenesis imperfecta, anterior facial height and maxillary length in type IV, as well as cranial base angle, posterior facial height and angulation between the jaws in type III. Our findings suggest that bisphosphonate therapy may positively enhance both mid-facial and mandibular craniofacial growth in individuals with osteogenesis imperfecta.